Large amplitude oscillatory shear induces crystal chain orientation in velocity gradient direction - Sreenivas, K.; Kumaraswamy, Guruswamy (ACS Macro Letters, 2014)
Imposition of large amplitude oscillatory shear (LAOS) on crystallizing polymer melts results in lamellar orientation in the shear gradient direction, in contrast to the flow-orientation observed for steady shear. LAOS enhances the formation of plate-like nuclei and orients their normals in the gradient direction. An Arrhenius temperature dependence (with activation energy approximate to 226 kJ/mol) characterizes the relaxation of crystal orientation with annealing.